The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0004-282x1999000500012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação e acompanhamento audiológico após meningite bacteriana

Abstract: RESUMO -A deficiência auditiva é uma das sequelas da meningite bacteriana que ocorre com maior frequência em crianças. Este estudo descreve o perfil audiológico (periférico e central) de crianças internadas com diagnóstico de meningite bacteriana. Nas 89 crianças que compareceram ao seguimento audiológico após a alta hospitalar e foram submetidas aos testes audiológicos, os resultados evidenciaram que 85,4% apresentaram acuidade auditiva normal em ambas orelhas, 10,1% apresentaram deficiência auditiva neurosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
1
0
0
1
Order By: Relevance
“…These differences between the groups were significant in the 0 and -10 relation. These findings agree with previous studies that found that children with unilateral HL present unilateral speech recognition performance significantly worse even in direct monaural conditions (in the better ear) when compared to CG, especially in most difficult relations of PSI test (5,30) .…”
Section: Pediatric Speech Intelligibility Test -Psi Testsupporting
confidence: 93%
“…These differences between the groups were significant in the 0 and -10 relation. These findings agree with previous studies that found that children with unilateral HL present unilateral speech recognition performance significantly worse even in direct monaural conditions (in the better ear) when compared to CG, especially in most difficult relations of PSI test (5,30) .…”
Section: Pediatric Speech Intelligibility Test -Psi Testsupporting
confidence: 93%
“…A tendência atual em relação a deficiên-cia auditiva se baseia no diagnóstico, etiologia e tratamento dentro do espectro de doenças otoló-gicas e neurotológicas encontradas em pacientes pediátricos, além de testes de triagem neonatal e na infância, visando a reabilitação auditiva precoce 16 . Em nossa amostra populacional a incidência da perda auditiva foi significativa, concordando com os achados descritos por Couto et al 17 que realizaram a avaliação auditiva central e periférica de 89 crianças acometidas por meningite, identificando em 10,1% perda sensorioneural bilateral, condizente com os resultados apresentados em nosso estudo.…”
unclassified